Pengaruh Pendidikan Kesehatan Perawatan Kaki terhadap Pengetahuan Penderita Diabetes Mellitus di Desa Tulehu Kecamatan Salahutu Kabupaten Maluku Tengah Tahun 2021 - Maritje Seflin J Malisngorar; Ira Sandi Tunny (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2021)
Diabetic ulcers are long-term complications in people with diabetes mellitus, so foot care is needed as a preventive measure. Patients with diabetes mellitus in Tulehu village, Salahutu sub district, Central Maluku district, have never received information about foot care, so foot care is never done except for nail cutting. This study aims to determine the effect of health education on knowledge of people with diabetes mellitus in foot care in Tulehu Village, Salahutu District, Central Maluku Regency in 2021. This study used a pre-experimental research design with a one-group pre-test-post-test design approach. by using a simple random sampling method, amounting to 64 people. The research instrument used a questionnaire. Data analysis used bivariate analysis and the significance level was 0.05. The results in this study obtained that there was an effect of health education on the knowledge of people with diabetes mellitus in foot care in Tulehu Village, Salahutu District, Central Maluku Regency in 2021